Usefulness of vaginal cytology tests in women with previous hysterectomy for benign diseases: assessment of 53,891 tests - Vale, Diama Bhadra; Braganca, Joana Froes; Caldeira Xavier-Junior, Jose Candido [UNESP]; Dufloth, Rozany Mucha [UNESP]; Derchain, Sophie; Zeferino, Luiz Carlos (Elsevier B.V., 2015)
Objective. To assess the value of vaginal screening cytology after hysterectomy for benign disease.Methods. This cross-sectional study used cytology audit data from 2,512,039 screening tests in the metropolitan region of Campinas from 2000 to 2012; the object was to compare the prevalence of abnormal tests in women who had undergone a hysterectomy for benign diseases (n = 53,891) to that of women who had had no hysterectomy. Prevalence ratios (95% confidence intervals, 95% Cl) were determined, and chi-square analysis, modified by the Cochrane-Armitage test for trend, was used to investigate the effects of age.Results. The prevalence of atypical squamous cells (ASC), low-grade squamous intraepithelial lesion (LSIL), and high-grade squamous intraepithelial lesion or squamous-cell carcinoma (HSIL/SCC) was 0.13%, 0.04% and 0.03%, respectively, in women who had undergone hysterectomy, and 0.93%, 0.51% and 0.26% in women who had not undergone hysterectomy. The prevalence ratios for ASC, LSIL and HSIL/SCC were 0.14(0.11-0.17), 0.08 (0.06-0.13) and 0.13 (0.08-020), respectively, in women with a hysterectomy versus those without. For HSIL/SCC, the prevalence ratios were 0.09 and 029, respectively, for women <50 or >= 50 years. The prevalence rates in women with a previous hysterectomy showed no significant variation with age.Conclusion. The prevalence rates of ASC, LSIL and HSIL/SCC were significantly lower in women with a previous hysterectomy for benign disease compared with those observed in women with an intact uterine cervix. This study reinforces the view that there is no evidence that cytological screening is beneficial for women who have had a hysterectomy for benign disease. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Uterine cervical neoplasms; Mass screening; Hysterectomy; Vaginal neoplasms; Guideline adherence